Schema benefit vs. proactive interference: Contradicting behavioral outcomes and coexisting neural patterns - Oren, Noga; Shapira-Lichter, Irit; Lerner, Yulia; Tarrasch, Ricardo; Hendler, Talma; Giladi, Nir; Ash, Elissa L. (NeuroImage (Orlando, Fla.), 2017)
Prior knowledge can either assist or hinder the ability to learn new information. These contradicting behavioral outcomes, referred to as schema benefit and proactive interference respectively, have been studied separately. Here we examined whether the known neural correlates of each process coexist, and how they are influenced by attentional loading and aging. To this end we used an fMRI task that affected both processes simultaneously by presenting pairs of related short movies in succession. The first movie of each pair provided context for the second movie, which could evoke schema benefit and/or proactive interference. Inclusion of an easy or hard secondary task performed during encoding of the movies, as well as testing both younger (22–35y) and older (65–79y) adults, allowed examining the effect of attentional load and older age on the neural patterns associated with context. Analyses focused on three predefined regions and examined how their inter-subject correlation (inter-SC) and functional connectivity (FC) with the hippocampi changed between the first and second movie. The results in the medial prefrontal cortex (mPFC) and posterior cingulate cortex (PCC) matched and expanded previous findings: higher inter-SC and lower FC were observed during the second compared to the first movie; yet the differentiation between the first and second movies in these regions was attenuated under high attentional load, pointing to dependency on attentional resources. Instead, at high load there was a significant context effect in the FC of the left ventrolateral prefrontal cortex (vlPFC), and greater FC in the second movie was related to greater proactive interference. Further, older adults showed context effect in the PCC and vlPFC. Intriguingly, older adults with inter-SC mPFC patterns similar to younger adults exhibited schema benefit in our task, while those with inter-SC PCC patterns similar to younger adults showed proactive interference in an independent task. The brain-behavior relationships corroborate the functional significance of these regions and indicate that the mPFC mainly contributes to schema benefit, while the left vlPFC and PCC contribute to proactive interference. Importantly, our findings show that the functions of the regions are retained throughout the lifespan and may predict the predominant behavioral outcome. •mPFC is related to schema benefit, the left vlPFC and PCC to proactive interference.•The mPFC and PCC showed context effect at low, but not at high attentional load.•The left vlPFC showed context effect at high load related to proactive interference.•Older adults showed proactive interference responses in the PCC.•The functions of the regions are retained with age and predict behavioral outcome.